Design of novel starch-based Pickering emulsions as platforms for skin photoprotection - Marto, J.; Gouveia, L. F.; Gonçalves, L.; Chiari-Andréo, B. G. [UNESP]; Isaac, V. [UNESP]; Pinto, P.; Oliveira, E.; Almeida, A. J.; Ribeiro, H. M. (Elsevier, 2016)
Green coffee oil and modified starch were recently found to have an enhanced protection effect against UV radiation. Therefore, this work aimed to develop an innovative sunscreen formulation based on Pickering emulsions concept, i.e., surfactant-free emulsions stabilized by physical UV filters associated natural oils as a key strategy for prevention against UV-induced skin damage. The Pickering emulsions of different compositions were characterized in terms of pH, mechanical, physical and microbiological stability by a thorough pharmaceutical control. In addition, the sun protection factor (SPF) as well as the in vitro and in vivo biological properties of the final formulations, including Episkin®, HRIPT and sunscreen water resistance. Formulation studies demonstrated the addition of physical UV filters was beneficial, leading to the inclusion of ZnO and TiO2 to ensure a high SPF against UVA and UVB, respectively. Although starch particles presented no intrinsic photoprotection properties, they proved to be a SPF promoter by a synergistic effect. Green coffee oil was the selected natural oil due to the highest SPF, when compared to other natural oils tested. Besides the excellent sunscreen activity confirmed by in vitro and in vivo results, the final formulations proved to be also suitable for topical use according to the rheological assessment and stability throughout the study period (3 months). In conclusion, the combination of three multifunctional solid particles and green coffee oil, contributed to achieve a stable and effective innovative sunscreen with a wide range of UV radiation protection.
Keywords: Broad-spectrum Pickering sunscreen; Natural ingredients; Photoprotection; Physical UV filters; Water resistance